Assessing the impact of tidal changes on fish environmental DNA metabarcoding in temperate and tropical coastal regions of Japan - Shin-ichiro Oka; Tetsuya Sado; Masayuki Ushio; Masaki Miya (Metabarcoding and Metagenomics)
Environmental DNA (eDNA) analysis is a valuable tool for detecting species presence in coastal environments. However, its effectiveness can be influenced by factors such as diffusion and degradation after being released by organisms. Understanding eDNA dynamics in response to tidal currents is pivotal, especially in the intertidal zone where water movement is pronounced. This study assessed the impact of tidal movements on fish eDNA metabarcoding across two regions separated by a 10-degree latitude difference: the temperate Boso Peninsula (35°N) and the tropical Motobu Peninsula (25°N). Over two days, we conducted four rounds of water sampling at three sites within 20 km of each Peninsula’s coast during substantial tidal differences (1.5–2 m), covering both outgoing and incoming tides. Fish eDNA metabarcoding analysis revealed notable differences in fish community compositions between the two Peninsulas, with statistically significant variations amongst the three sites within each Peninsula. At each site, comparison between outgoing and incoming tides showed significant differences at five of the six sites. However, variation partitioning analysis suggested that the impact of tidal changes was limited compared to other factors in both regions. These findings suggest that tidal movements may not be a critical factor in designing sampling plans for comparing fish community structures through eDNA metabarcoding at this spatial and temporal scale. Additionally, they highlight the need for empirical studies to explore the underlying mechanisms driving differences in eDNA-based fish community composition related to tidal changes.